2009
DOI: 10.1080/14459790802652183
|View full text |Cite
|
Sign up to set email alerts
|

Responsible gambling signage on electronic gaming machines, before and after the implementation of the United Kingdom Gambling Act: an observational study

Abstract: ABSTRACT. The 2005 Gambling Act in Britain requires

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 21 publications
(21 reference statements)
0
8
0
Order By: Relevance
“…Stewart & Wohl found that pop‐up reminder messages improved spend‐limit adherence. In real‐world settings, however, the effect may be smaller , and may diminish with repeated exposure . Careful tailoring of message presentation could enhance these tools’ effectiveness: eye‐tracking results could be used to optimize on‐screen message delivery both spatially (by AOI) and temporally (by phase or outcome) to coincide with gamblers’ attention.…”
Section: Discussionmentioning
confidence: 99%
“…Stewart & Wohl found that pop‐up reminder messages improved spend‐limit adherence. In real‐world settings, however, the effect may be smaller , and may diminish with repeated exposure . Careful tailoring of message presentation could enhance these tools’ effectiveness: eye‐tracking results could be used to optimize on‐screen message delivery both spatially (by AOI) and temporally (by phase or outcome) to coincide with gamblers’ attention.…”
Section: Discussionmentioning
confidence: 99%
“…In theory, more passive approaches to promoting responsible gambling behaviour, such as posters, signs, leaflets and brochures, can reach a wider audience in less time than Advisors speaking one-on-one with casino patrons. However, such responsible gambling signage is not always posted in visible places (Moodie and Reith, 2009), and a more general limitation is that public health signage alone often does not impact behaviour (e.g. Beaudoin et al, 2007; Dingman et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…3 In its review of the implementation of the 2005 Act, the Culture, Media and Sport Committee (CMS Committee) found no evidence "that the onshore gambling industry is conducted in a way which is not fair and transparent to the consumer" (House of Commons, 2012, paragraphs 16 and 18). Anecdotal evidence suggests that not all players are aware of these requirements; for this reason alone compliance with them is essential if players are to be informed about the risks they take (Moodie & Reith, 2009), for as BGPS 2010 shows, problem gambling is significantly associated with education levels, "rates being higher among those with lower levels of educational attainment" (Wardle et al, 2011b, p. 85).…”
Section: Responsible To Whom About Whatmentioning
confidence: 96%